If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 9 = 3x + -37 Reorder the terms: 9 + x = 3x + -37 Reorder the terms: 9 + x = -37 + 3x Solving 9 + x = -37 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 9 + x + -3x = -37 + 3x + -3x Combine like terms: x + -3x = -2x 9 + -2x = -37 + 3x + -3x Combine like terms: 3x + -3x = 0 9 + -2x = -37 + 0 9 + -2x = -37 Add '-9' to each side of the equation. 9 + -9 + -2x = -37 + -9 Combine like terms: 9 + -9 = 0 0 + -2x = -37 + -9 -2x = -37 + -9 Combine like terms: -37 + -9 = -46 -2x = -46 Divide each side by '-2'. x = 23 Simplifying x = 23
| 8034*n=80.34 | | 0.5d-0.83d=4 | | 8(7x-1)=64 | | 3x-9=6x+36 | | 4x=(23x+18) | | 12x^2-200=0 | | 14-2x=-5x | | m+4=6.7 | | 3x-11=x+3 | | -5a+6a=56 | | 130=4x+x+120 | | 63x^2-6x-9=0 | | 8a^2(6-3a^2)= | | 6.8-4.2x=5.6x-3 | | 2-2(1-2x)=12(10+x)-3x | | 2+4x+1= | | 3(2+5g)-10=-22+6g | | -3*(h+1.4)=11*(5-h) | | 9x+3x-10=3x+x | | x^2+8x+64= | | -9y=-.162 | | -4(5x-1)=4(-4x-10) | | 35-8x=15+12x | | (T+8)(-2)=64 | | 35-8x=1512x | | -79=-23+7x | | 35-8x=15-12x | | y=124x | | 35+4n=95 | | 7x=175+7y | | -130x=120 | | 11-3x-6= |